2015
DOI: 10.1177/1532673x15594232
|View full text |Cite
|
Sign up to set email alerts
|

Campaign Money, Congress, and Perceptions of Corruption

Abstract: Many Americans think campaign money has a corrupting influence on Congress. Yet how they think about money in politics is a relatively unexplored topic. This article investigates how the public reasons about campaign money and corruption. Our survey experiments demonstrate that attitudes about campaign money are structured by partisan interest and are also driven by information about sources of campaign money and the amount spent (particularly for large independent expenditures made possible by Citizens United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Redlawsk and McCann (2005: 275–277) find two different conceptualizations of corruption: ‘corruption-as-lawbreaking’ and ‘corruption-as-favoritism’. Indeed, Bowler and Donovan (2016) and Atkinson and Bierling (2005) find evidence supporting definitions beyond corruption-as-lawbreaking. For example, Bowler and Donovan (2016: 289) claim that ‘majorities of respondents surveyed for this study found a number of legal (and illegal) arrangements that financed congressional campaign ads to be somewhat corrupt or corrupt’.…”
Section: Background and Theoretical Expectationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Redlawsk and McCann (2005: 275–277) find two different conceptualizations of corruption: ‘corruption-as-lawbreaking’ and ‘corruption-as-favoritism’. Indeed, Bowler and Donovan (2016) and Atkinson and Bierling (2005) find evidence supporting definitions beyond corruption-as-lawbreaking. For example, Bowler and Donovan (2016: 289) claim that ‘majorities of respondents surveyed for this study found a number of legal (and illegal) arrangements that financed congressional campaign ads to be somewhat corrupt or corrupt’.…”
Section: Background and Theoretical Expectationsmentioning
confidence: 94%
“…Indeed, Bowler and Donovan (2016) and Atkinson and Bierling (2005) find evidence supporting definitions beyond corruption-as-lawbreaking. For example, Bowler and Donovan (2016: 289) claim that ‘majorities of respondents surveyed for this study found a number of legal (and illegal) arrangements that financed congressional campaign ads to be somewhat corrupt or corrupt’. As such, both legal and illegal corruption must be considered.…”
Section: Background and Theoretical Expectationsmentioning
confidence: 94%
“…More than affecting evaluations of Congress as a whole, scholars have also argued that campaign finance may alter voter's perceptions of individual candidates. For example, after conducting a survey experiment, Bowler and Donovan (2016) find that beliefs about how trustworthy or corrupt campaign contributions are dependent on the source of the contributions. As a whole, they find that contributions of identical amounts made to candidates by corporations and unions are perceived as more corrupt than contributions made by individuals.…”
Section: Perceptions About Money In Politicsmentioning
confidence: 99%
“…Such signaling effects through the media have been well-documented (Iyengar and Kinder 1989), and voters see small-dollar donations from individuals as more honest (Bowler and Donovan 2016). Indeed, Ella Nilsen (2019) reported that Elizabeth Warren "swore off PAC money to make a statement" in a story for Vox.com.…”
Section: Perceptions About Money In Politicsmentioning
confidence: 99%
“…As we note below, many people see Congress as corrupt. Previous work discusses how public perceptions of corruption differ from what is illegal, and examine how various modes of financing congressional campaigns may be seen by the public as corrupt or not (e.g., Bowler & Donovan, 2016). This work extends on that by examining how attitudes about campaign finance affect how people view representation and Congress.…”
Section: Introductionmentioning
confidence: 99%